NILAI-NILAI PENDIDIKAN ISLAM DALAM PEMIKIRAN FILSAFAT MOHAMMAD IQBAL - Suripto (LPPM STAI Muhammadiyah Probolinggo, 2023)
Muhammad Iqbal is a modern Muslim philosopher-poet who, conceptually and philosophically, does not have a detailed formulation of Islamic educational concepts. However, implicitly, based on his fundamental views on humanity, particularly his philosophical thoughts on the ego, a dynamic, innovative, and vitalistic concept of Islamic educational thought can be reconstructed. The genealogy of Islamic educational values in Iqbal's philosophical thought is rooted in his ideas about humanity, especially his perspective on the story of Adam, the concept of ego, and the perfect human (insan kamil). Based on this, fundamental issues in humanities studies related to education can be identified: innate potential, freedom, and the essence of humanity. The construction of Islamic educational values in Muhammad Iqbal's philosophical thought includes: values of monotheistic education, values of moral education, values of rational education (intelligence), and values of social education. All of these educational values also originate from Iqbal's view of the liberated ego, constantly progressing towards perfection, which is Allah SWT. Keywords: Values; Islamic Education; Philosophical Thought; Iqbal.